Geohazards & Remediation - Huang, Yu.; Casagli, Nicola; Tappin, David; Sun, Jin.; Lu, Ping.; Mao, Wuwei; Li, Xingyue; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Higher Education Press, co-published with Springer.)
Geohazards & Remediation aims to establish a platform for scientists and engineers in the field of geohazards and remediation. This journal focuses on key issues of geohazards such as the mechanisms, prevention and control, risk analysis, monitoring and early warning, and emergency response, as well as post-disaster recovery and reconstruction. The journal will present advanced theoretical, experimental and field and AI-aided research on geological disasters and their remediation. The journal encourages submissions on topics including, but not limited to, mechanisms of geohazards, geohazard forecasting, geohazard mitigation, resilient disaster prevention, chains of geohazards.
Keywords: Natural disasters; Engineering; Earth sciences; Physical geography; Geophysics; Earth sciences; Geography; Natural Hazards; Technology and Engineering; Earth Sciences; Earth System Sciences; Geophysics; Earth and Environmental Sciences